Effect of ferrite content on dissolution kinetics of gibbsitic bauxite under atmospheric pressure in NaOH solution - Yang, Hui-bin; Pan, Xiao-lin; Yu, Hai-yan; Tu, Gan-feng; Sun, Jun-min (Journal of Central South University, 2017)
The dissolution property of high-ferrite gibbsitic bauxite and the effect of ferrite content on the dissolution kinetics of gibbsitic bauxites in sodium hydroxide solution under atmospheric pressure from 50 to 90 °C were systematically investigated. The dissolution property of high-ferrite gibbsitic bauxite is increased by increasing the dissolution temperature and the NaOH concentration or decreasing the particle size of bauxite, which is easy to dissolve under atmospheric pressure. The kinetic equations of gibbsitic bauxites with different ferrite contents during the dissolution process at different temperatures for different times were established, and the corresponding activation energies were calculated. The ferrite in the gibbsitic bauxite reduces the dissolution speed and increases the activation energy of dissolution, the diffusion process of which is the rate-controlling step.